2013
DOI: 10.4103/0300-1652.114590
|View full text |Cite
|
Sign up to set email alerts
|

Integrating cervical cancer screening with HIV care in a district hospital in Abuja, Nigeria

Abstract: Background:Human immunodeficiency virus positive (HIV+) women have a higher risk of developing invasive cervical cancer compared with uninfected women. This study aims to document programmatic experience of integrating cervical cancer screening using Visual Inspection and Acetic Acid (VIA) into HIV care as well as to describe patients’ characteristics associated with positive VIA findings amongst HIV+ women.Materials and Methods:A cross-sectional study analysed routine service data collected at the antiretrovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 54 publications
1
50
0
Order By: Relevance
“…Resources described include: material to provide education and support to patients [5, 28, 34, 40]; staff to operate the referral system [28, 30]; staff to coordinate integration[28]; forms or electronic medical records [4, 36]; and medical and adequate infrastructure, including consistent electricity and water supply.…”
Section: Resultsmentioning
confidence: 99%
“…Resources described include: material to provide education and support to patients [5, 28, 34, 40]; staff to operate the referral system [28, 30]; staff to coordinate integration[28]; forms or electronic medical records [4, 36]; and medical and adequate infrastructure, including consistent electricity and water supply.…”
Section: Resultsmentioning
confidence: 99%
“…Cervical cancer services were integrated into HIV/AIDS programming in six African countries: Ethiopia, Kenya, Malawi, Tanzania, Zambia, Zimbabwe (program data, unpublished). In Zambia, Malawi, and Botswana, screening and cryotherapy services were integrated into existing national HIV/AIDS care and treatment programs, resulting in increased coverage of screening and treatment services for HIV‐positive women .…”
Section: Resultsmentioning
confidence: 99%
“…25 Forwomenwhorequirehigher-levelcare(suchasbiopsy,surgery, or radiotherapy) the dearth of trained providers, lack of equipment, highcostofservices,andlackofastandardizedreferralsystemhave asignificantimpactonmorbidityandmortalityofwomen.InNigeria, nearly 70% of VIA-positive women were unable to access treatment services at tertiary facilities owing to high financial costs of treatment. 20 Often treatment for invasive cervical carcinoma is only availableatasingletertiaryfacility,locatedinthecapital. 19 Theavailability of higher-level services is even more critical for HIV-positive women,astheyaremorelikelytohaveextensivelesionsthatdonot meetthecriteriafortreatmentwithcryotherapy.…”
Section: Lack Of Availability Of Cervical Cancer Treatment Servicesmentioning
confidence: 99%
“…Duber et al found that vertical programs, even on the scale of PEPFAR, may not impact health outcomes that were not specifically targeted on a national level [12]. Attempts have been made to integrate donor-funded HIV prevention, care, and treatment programs into national health systems to ensure efficiency and sustainability, including: TB [13••, 14], maternal-child health (MCH) [15–20], cervical cancer screening [21], sexually transmitted infection (STI) [16, 22], and family planning [23, 24] programs. In addition, ART has increased the life expectancy of people living with HIV, and HIV is now considered a chronic disease.…”
Section: Introductionmentioning
confidence: 99%